Awareness and practices of king Khalid university students in virtual clothing - Mohamed, Amani Shaaban Ali (Journal of Humanities & Social Sciences, 2023)
The study aims to identify the awareness and practices of King Khalid University students in virtual clothing. It also aims to find the individual differences between the level of awareness and the level of practices according to social and economic factors. The study sample consists of 345 students of King Khalid University in the Kingdom of Saudi Arabia. The study tools include a form of general data (age - sex - work - marital status - income level) and a questionnaire to measure awareness and practices. The study follows the descriptive analysis approach. Then data analysis and statistical treatments using the program (SPSS).The study has achieved a set of results. The most important is that there is a interaction between the level of awareness and the level of practice of virtual clothing at the level of a function of 0.01. There is a statistically significant relationship between the level of awareness and the level of practice according to working students in favor of working students at the level of significance 0.01, There is no statistically significant interaction between the level of awareness and the level of practice according to the income of university students. There is no statistically significant interaction between the level of awareness and the level of practice according to age ., There is a statistically significant interaction between the level of awareness and the level of practice according to sex in favor of females at the level of significance 0.01, There is a statistically significant interaction between the level of awareness and the level of practice according to social status in favor of unmarried people at the level of significance 0.01.
Keywords: Awareness; Practices; Virtual Reality; Virtual Clothing